2015
DOI: 10.1128/jcm.01985-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Laboratory Identification, and In Vitro Antifungal Susceptibility of Yarrowia (Candida) lipolytica Isolates Causing Fungemia: a Multicenter, Prospective Surveillance Study

Abstract: iOur case series showed that uncomplicated Yarrowia lipolytica fungemia might be treated with catheter removal alone. The Vitek 2 YST identification (ID) card system, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), and internal transcribed spacer and 25S nuclear ribosomal DNA (nrDNA) gene sequencing provided reliable identification. All isolates had low MICs to voriconazole, echinocandins, and amphotericin B.A growing number of non-albicans Candida spp. have emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In India, C. tropicalis has the distinction of being the most common infecting species [5]. On the other hand, C. lipolytica is a relatively obscure NAC species considered to be of low virulence, but it is emerging as an important cause of nosocomial infections [6]. Both NAC species isolated from our patient were fluconazole resistant, in keeping with the belief that NAC are generally less susceptible to fluconazole.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In India, C. tropicalis has the distinction of being the most common infecting species [5]. On the other hand, C. lipolytica is a relatively obscure NAC species considered to be of low virulence, but it is emerging as an important cause of nosocomial infections [6]. Both NAC species isolated from our patient were fluconazole resistant, in keeping with the belief that NAC are generally less susceptible to fluconazole.…”
Section: Discussionsupporting
confidence: 79%
“…With regard to catheter removal, its role in the management of candidemia is especially imperative if it is the source of infection. In fact, for some patients with C. lipolytica fungemia, catheter removal alone (i.e., without the administration of any antifungal agent) has been sufficient in clearing the fungemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, databases consisting of protein mass spectra from over 2,400 microbial species are commercially available [ 106 , 107 ], making the identification of a wide range of microorganisms possible. Given its numerous advantages, MALDI–TOF MS has been gaining popularity for identification of pathogenic microorganisms, including bacteria [ 108 , 109 ], yeasts [ [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] ] and even filamentous fungi [ 109 , [116] , [117] , [118] ], in clinical microbiology laboratories. The potential of this technology in diagnosing Aspergillus , Penicillium and Talaromyces species has also been evaluated by numerous studies.…”
Section: Species Recognition/identification and Current Advancesmentioning
confidence: 99%
“…Voriconazole was used in our study to treat C. parapsilosis, C. lipolytica and C. guilliermondii, which lowered the mortality rate and tissue burden in the mice organs. Zhao et al, (33) reported that fluconazole, itraconazole and posaconazole should not be used to treat C. lipolytica, but voriconazole may be useful for treatment. Our results agree with a previous experimental murine infection by C. guilliermondii where voriconazole was reported to be experimentally effective (34).…”
Section: Discussionmentioning
confidence: 99%